Ratio of Root(3) Terms

Algebra Level 2

What does the following expression evaluate to?

3 + 1 ( 3 + 2 ) ( 3 1 ) \large{\frac{\sqrt{3} + 1}{(\sqrt{3} + 2)(\sqrt{3} -1)}}


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

3 + 1 ( 3 + 2 ) ( 3 1 ) ( 3 + 1 ) ( 3 + 1 ) ( 3 + 2 ) ( 3 1 ) ( 3 + 1 ) \frac {\sqrt{3}+1}{(\sqrt{3}+2)(\sqrt{3}-1)} \Rightarrow \frac { (\sqrt{3}+1)(\sqrt{3}+1)}{(\sqrt{3}+2)(\sqrt{3}-1)(\sqrt{3}+1)}

= 3 + 2 3 + 1 ( 3 + 2 ) ( 3 1 ) = 4 + 2 3 ( 3 + 2 ) 2 = \frac {3+2\sqrt{3}+1}{(\sqrt{3}+2)(3-1)} = \frac {4+2\sqrt{3}}{(\sqrt{3}+2) \cdot 2}

= 2 ( 3 + 2 ) 2 ( 3 + 2 ) = \frac {2\cdot (\sqrt{3}+2)}{2 \cdot (\sqrt{3}+2)}

= 1 = 1

Did the same way

I Gede Arya Raditya Parameswara - 4 years, 4 months ago
Genis Dude
Feb 10, 2017

Expandind the denominator ,

(√3+2)(√3-1)

→3+2√3-√3-2

→√3+1

Therefore,

denominator and numerator are same

So required answer is 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...